PERTUMBUHAN DAN PRODUKSI MENTIMUN (Cucumis sativus L.) AKIBAT PEMBERIAN MACAM DAN DOSIS PUPUK KANDANG: GROWTH AND PRODUCTION OF CUCUMBER (Cucumis sativus L.) DUE TO THE TYPE AND DOSAGE OF CAGE FERTILIZER - Junaidi; supandji; Nugraheni Hadiyanti (Agrifarm : Jurnal Ilmu Pertanian, 2021)
Cucumber is one of the important vegetable commodities that have high nutritional value and is alternative medicine. To increase the productivity of both plants and the land where plants are grown, organic fertilization is needed. Manure is an organic fertilizer to increase soil fertility so that plant growth increases. Giving different types of manure with different doses will result in different plant growth and development. The purpose of this study was to determine the effect of the interaction between the type and dose of manure treatment on the growth and production of cucumbers. This study is a factorial experiment with two factors, which were arranged according to a completely randomized design (CRD) and repeated 3 (three) times. The first factor is the type of manure consisting of 3 levels, namely: chicken manure (K1), cow manure (K2), and goat manure (K3). The second factor is the dose of manure which consists of 3 levels, namely: 10 tons/ha (D1), 15 tons/ha (D2), and 20 tons/ha (D3). Observational data were analyzed by analysis of variance to determine the effect of the treatment on the observed parameters. After knowing the effect of treatment on the observed parameters, it is continued with the Least Significant Difference (BNT) test at the 5% level if it is significantly different. The combination of types and doses of manure significantly affected plant height, number, and leaf area at the age of observation 21 and 28 DAP, number of fruits, and fruit production per plant. The combination of the type of manure and the dose of manures did not significantly affect the number of leaves at 14 days of age, fruit length, fruit diameter, and fruit weight. The combination of goat manure at a dose of 20 tons/ha resulted in the best growth and production of cucumbers.